The effects of water sample treatment, preparation, and storage prior to cyanotoxin analysis for cylindrospermopsin, microcystin and saxitoxin. (25th February 2016) - Kamp, Lisa; Church, Jennifer L.; Carpino, Justin; Faltin-Mara, Erin; Rubio, Fernando
Abstract: Cyanobacterial harmful algal blooms occur in freshwater lakes, ponds, rivers, and reservoirs, and in brackish waters throughout the world. The wide variety of cyanotoxins and their congeners can lead to frequent exposure of humans through consumption of meat, fish, seafood, blue-green algal products and water, accidental ingestion of contaminated water and cyanobacterial scum during recreational activities, and inhalation of cyanobacterial aerosols. Cyanotoxins can also occur in the drinking water supply. In order to monitor human exposure, sensitive analytical methods such as enzyme linked immunosorbent assay and liquid chromatography-mass spectrometry are often used. Regardless of the analytical method of choice, some problems regularly occur during sample collection, treatment, storage, and preparation which cause toxin loss and therefore underestimation of the true concentration. To evaluate the potential influence of sample treatment, storage and preparation materials on surface and drinking water samples, the effects of different types of materials on toxin recovery were compared. Collection and storage materials included glass and various types of plastics. It was found that microcystin congeners LA and LF adsorbed to polystyrene, polypropylene, high density polyethylene and polycarbonate storage containers, leading to low recoveries (<70%), cylindrospermopsin and saxitoxin did not adsorb to the containers tested. Therefore, this study shows that glass or polyethylene terephthalate glycol containers are the materials of choice for collection and storage of samples containing the cyanotoxins cylindrospermopsin, microcystins, and saxitoxin. This study also demonstrated that after 15 min chlorine decreased the concentration of microcystin LR to <40%, microcystin LA and saxitoxin to <15%, therefore quenching of drinking water samples immediately upon sample collection is critical for accurate analysis. In addition, the effect of various drinking water treatment chemicals on toxin recovery and the behavior of those chemicals in the enzyme linked immunosorbent assays were also studied and are summarized. Highlights: Absorption of the microcystin congeners LR, LA, LF to plastic storage containers. Effect of chlorine on microcystins LR, LA, LF, saxitoxin and cylindrospermopsin concentration. Tolerance of drinking water treatment chemicals on cyanotoxin ELISAs.